(untitled) (Research, Society and Development, 2021)
The use of non-thermal plasma in food raw materials is recent and may constitute an innovation for the sector, which needs to generate knowledge about this subject, in order to know the possibilities of using this emerging technology applied in food. The objective of this study was to evaluate the technological behavior in flour and wheat bran, treated in a non-thermal plasma generator, obtained by microwave, compared with the same raw materials without treatment. The non-thermal plasma was generated by microwaves from 200 W of power and the gas used was argon. The system operated at atmospheric pressure. Wheat flour treated by non-thermal plasma (FPL) showed a lower percentage of damaged starch (4.33%), a lower accumulated size distribution at D90% and a lower size distribution of particle, in addition to lower values for its pasting properties, where all these characteristics showed that ANOVA differed significantly (p≤0.05) when compared to the control wheat flour (FC). The gluten of these two materials did not change significantly to the same significance. Wheat bran treated by non-thermal plasma (BPL) was evaluated using pH, water absorption index (WAI) and water solubility index (WSI) and instrumental color analysis, with the achievement of L* parameters, a* and b*, in addition to the color difference (ΔE) and these results were compared for untreated bran (BC). Only the WAI and the b* parameter of the instrumental color analysis showed a significant difference for ANOVA (p≤0.05) in comparison with BC. Despite having a significant difference in a color analysis parameter (b*), the color difference between the samples (ΔE = 0.30) showed a value below 1.0, which indicates that this difference is difficult to perceive by the observer. The results show important changes for these raw materials and that need further experimental and analytical deepening to consolidate the effects conferred by this emerging technology.